In search of alternative frameworks the experience of Save the Children UK's NGO partners in early childhood care and development - Pura, Alexandra (Quezon City Paperchase Print Services, 2001)
"This book brings together the experience of SC-UK and its partners in early childhood care and development (ECCD), taking into account the content and methodology developed, ways of working, and advocacy strategies in relation to the local context of each partner. It also attempts to assess and identify the different ECCD models used by the partners in the hope of defining the "alternative" framework. Lastly, it identifies good models of practice and draws up recommendations for further improving the work."--Executive summary.
Acknowledgments -- Foreword -- Acronyms -- Executive summary -- Introduction -- Training in non-traditional alternative ECCD for barangay daycare workers in Region XI : Notre Dame of Dadiangas College-Early Childhood Education Centre -- Community-based early childhood care and development programme in urban poor communities : Harnessing Self-Reliant Initiatives and Knowledge, (HASIK) Inc. -- Drama in education and children's theatre method and Convention on the Rights of the Child integration in the ECCD curriculum in Region IV : Children's Laboratory for Drama in Education Foundation -- Synthesis : in search of alternative frameworks -- Conclusion : evolving standards in ECCD work -- Bibliography -- About the author.
"This publication was made possible with the assistance of Save the Children Sweden.
Keywords: Chid care -- Philippines; Child development -- Philippines; School age child care -- Philippines